Utilisation of Natural Zeolites for Air Separation and Pollution Control - Wang, Shaobin (Bentham Science Publishers, 2012)
Natural zeolites are abundant and low cost materials available all over the world. Due to their highly developed porous structure, these materials exhibit high capacity for gas adsorption and selectivity for separation. In the report, the structure and characteristics of natural zeolites related to gas adsorption and their application in gas separation are briefly reviewed. Natural zeolites can be used for gas drying due to having high adsorption capacity of water. They can also be used for cleaning of natural gas and flue gas.